194k views
3 votes
Help! Exponential Equation WITHOUT CALCULATOR

Help! Exponential Equation WITHOUT CALCULATOR-example-1

1 Answer

3 votes

1. (2^(x) -2^(-x))^(2) = 4^(2) \\ \\2^(2x)-2*2^(x)*2^(-x) + 2^(-2x) =4^(2) \\ \\2^(2x)-2*2^(x-x) + 2^(-2x) =4^(2) \\ \\ 2^(2x)+ 2^(-2x) - 2=16 \\ \\ 2^(2x)+ 2^(-2x) = 18 \\ \\ 2.( 2^(x))^(3) - (2^(-x)^) ^(3)= (2^(x) -2^(-x))(2^(2x)+2^(x)*2^(-x)+2^(-2x)) \\ \\ ( 2^(x))^(3) - (2^(-x)^)^(3)=(2^(x) -2^(-x))(2^(2x)+2^(-2x)+2^(x)*2^(-x)) \\ \\ ( 2^(x))^(3) - (2^(-x)^)^(3)=(2^(x) -2^(-x))(2^(2x)+2^(-2x)+1) \\ \\ ( 2^(x))^(3) - (2^(-x)^)^(3)=(2^(x) -2^(-x))((2^(2x)+2^(-2x))+1)


\\ \\ ( 2^(x))^(3) - (2^(-x))^(3) =(4)((18)+1)= 76 \\ \\ 2^(3x)-2^(-3x) =76
User Jack Chu
by
6.0k points